Perilaku Konsumen Terhadap Minat Beli Pada Perubahan Paradigma Pasar Dari Konvensional Ke Digital - Lucky Mahesa Yahya; Erizal Nazaruddin; Olivia Vransiska Cania; Dhea Sri Amanda; Widia Khairani (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This study's objectives are to ascertain the findings from a comparison of the effectiveness of using digital marketing vs traditional marketing, as well as to give a general overview of how to use digital marketing to boost sales volume. We employed sample counting with the Multiple Linear approach, which was processed using SPSS 26.0 and the EPIC Model method, in this investigation because we needed about 100 respondents. Using an online questionnaire was the study's method for gathering data. According to research findings, using digital marketing to promote products might enhance potential buyers' understanding of the things being promoted and their interest in purchasing them. The Multiple Linear Regression test findings indicate that the conventional market (X2) and the digital market (X1) have a favourable impact on customer buying interest (Y). From the results Cronach alpha values for X1, X2, and Y are based on the table mentioned above and have a significance level of 0.05 df = 100 - 2 = 98 = 0.1654. In the EPIC Model method, the effectiveness level of the Digita Market variable is higher at 4.07 when compared to the Conventional Market variable, which is 3.63.